The Owadów-Brzezinki geoeducation area at Sławno - Błażejowski, Błażej; Wierzbowski, Andrzej (Geotourism/Geoturystyka, 2021)
The geoeducation area (called also “Owadów-Brzezinki Geopark”) located in the north-western margin of the Holy Cross Mountains (Tomaszów Syncline) at Sławno community (Łódź Voivodeship), was established in June 2019, in close vicinity of the Owadów-Brzezinki quarry. This locality is one of the most important palaeontological sites described recently in Poland. The area consists of the exhibition pavilion, educational routs and panoramic viewing platform, which is located along the edge of the quarry. The palaeontological exhibition shows the unique Late Jurassic fossils of marine and terrestrial organisms, many of them new to science, that have been excavated in the quarry during the last eight years. Among the most important fossils are: ammonites, lobster-like decapod crustaceans, horseshoe crabs, actinopterygian fish, a cryptodiran turtle, ichthyosaurs, as well as a small terrestrial crocodyliform, pterosaurs and insects. In addition to the original fossils, the exhibition presents life-size reconstructions of animals, that inhabited the local seas and islands during the Late Jurassic. The palaeontological sites of Owadów-Brzezinki is referred to as a new “taphonomic window” of the Late Jurassic, providing insights about the evolution of life on Earth in the palaeogeographical and palaeoenvironmental context.